Analysis of Collaboration, Communication, Critical Thinking, and Creative Thinking Ability of Students in Solving Science Problems in Terms of Gender - Bahtiar Bahtiar*; Maimun Maimun; Ibrahim Ibrahim (Universitas Syiah Kuala, 2023)
This research is motivated by the existence of information related to the ability that students must possess today, namely collaboration, communication, critical thinking, and creative thinking ability. The purpose of this study was to analyze in more detail the students' 4C abilities in solving science problems in terms of gender. This research includes quantitative research involving the first-semester of science students of FTK UIN Mataram who are taking introductory physics courses. The participants used in this study were 67 students, of which 32 were male students and 35 were female students. Collaboration and communication ability are measured during the lecture process using observation sheets. Critical thinking and creative thinking were measured using written test questions with a description of 10 questions each. The data obtained were analyzed using descriptive statistics and Rash modeling. The results showed that female students' collaboration and creative thinking abilities were better than male students. The results also showed that male students' communication and critical thinking ability were better than female students. In general, the 4C abilities possessed by female students and male students are not much different